Social Work in a Digital Age: The Need to Integrate Social Media in Social Work Education in the UK - Charles Mugisha (Journal of Social Work Education and Practice, 2023)
The rise of social media provides a unique opportunity for social work to integrate new technologies in social work curriculum. Changes in social work curriculum require a catalyst and sound research evidence. Social media is in itself a catalyst for change because of its power for collaborative learning and social interaction. This paper explores the need to integrate social media in social work education by utilising a social learning model. The author argues that the new generation of social work students was born during the “digital age” and as such have been immersed in technology all their lives. There is need therefore for a social work curriculum that is relevant to today’s world of Facebook, Twitter, YouTube, WhatsApp, and LinkedIn.